Mechanical Properties of Clayey Sand Treated with Cement-Rubbershreds - Chan C.M. (Institute of Research and Community Outreach - Petra Christian University, 2012)
Residual soils of clayey sand composition can potentially be treated to construct a 2-layer pavement system. Using cement as the primary binder and recycled rubbershreds (<2 mm thick, 0.425 mm - 12 mm in length) as filler material, the improved ground can serve as a reliable road foundation, overlain with a surface capping layer. In order to determine the performance of this treated foundation layer, the relevant mechanical properties were examined using suitable laboratory tests, i.e. compaction, unconfined compressive strength and bender element tests. From the test results, it can be concluded that a mixture of cement and recycled rubbershreds effectively enhanced the mechanical properties of the soil. The cement dosage was kept at a minimum to bind the soil and rubbershreds for long term durability, while the rubbershreds served as a flexible filler material, without compromising the targeted strength and compressibility.